The Combined Prognostic Value of 18F‐FDG PET/CT Metabolic Parameters of Immune Organs and Hematological Immune‐Related Markers in Patients With Locally Advanced Cervical Cancer - Yi Li; Xin Wang; Yuanlin Li; Wanhu Li; Defeng Liu; Longxiang Guo; Xiuli Liu; Zhichao Li; Ao Liu; Minghuan Li (Cancer Medicine)
ABSTRACT Background This study aimed to explore the prognostic value of fluorine‐18 fluorodeoxyglucose positron emission tomography/computed tomography (18F‐FDG PET/CT) metabolic parameters of immune organs and hematological immune‐related markers for patients with locally advanced cervical cancer (LACC) undergoing concurrent chemoradiotherapy (CCRT), and to establish prognostic nomograms based on these potential biomarkers. Methods A total of 180 patients with LACC undergoing CCRT were retrospectively reviewed and randomly divided into training and validation groups at a 7:3 ratio. Cox regression analysis was performed to identify independent prognostic factors for progression‐free survival (PFS) and overall survival (OS) from hematological immune‐related markers and 18F‐FDG PET/CT metabolic parameters of the primary tumor, spleen, and bone marrow (BM). Nomograms were developed and evaluated using receiver operating characteristic curves, concordance index (C‐index), calibration curves, and decision curve analysis (DCA). Spearman correlation analysis was used to assess the relationships among metabolic parameters. Results Multivariable analysis identified International Federation of Gynecology and Obstetrics (FIGO) stage, neutrophil‐to‐lymphocyte ratio (NLR), and spleen maximum standardized uptake value (SUVspleen) as independent prognostic factors for PFS. For OS, the independent prognostic factors were FIGO stage, NLR, metabolic tumor volume, and SUVspleen. The nomograms demonstrated better prognostic performance for PFS (area under curve [AUC]: 0.875 and 0.862; C‐index: 0.809 and 0.775) and OS (AUC: 0.858 and 0.814; C‐index: 0.828 and 0.792) in the training and validation groups. Calibration curves and DCA indicated that the nomograms have good predictive accuracy and clinical utility. Spearman correlation analysis revealed significant positive correlations among total lesion glycolysis, SUVspleen, SUVBM, and platelet‐to‐lymphocyte ratio. Conclusion The nomograms based on metabolic parameters of immune organs and hematological immune‐related markers demonstrated high predictive value for patients with LACC undergoing CCRT. The observed correlations between the metabolic parameters of the primary tumor and immune organs suggest a widespread disturbance of systemic immunity caused by the tumor.